Direct C–H Arylation as a Chemoselective Single‐Step Access to π–Acceptor–π Type Building Blocks. Issue 21 (3rd November 2017) - Lu, Kuan‐Ming; Li, Wei‐Ming; Lin, Po‐Yu; Liu, Kuan‐Ting; Liu, Ching‐Yuan
Abstract: Different from the traditional multi‐step synthesis, a chemoselective direct C–H arylation is reported for the single‐step synthesis of various useful π–acceptor–π (π–A–π) type building blocks for use in organic electronics. This well‐optimized C–H heteroarylation exhibits good product yields, broad substrate scope, and high functional group compatibility. Applications in the efficient synthesis of a new metal‐free dye sensitizer for dye‐sensitized solar cells (DSSCs) are also demonstrated. Abstract :